Pidana Mati Terhadap Tipikor Perspektif Fikih Islam - Amir, Nurhikma; Shuhufi, Muhammad; P, Patimah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This article discusses how the death penalty for corruptors is based on Islamic law, what the theory of punishment in Islamic law is for criminal acts of corruption, and what the death penalty for corruptors is in Islamic law. The research method used is library research, namely by searching and collecting data from libraries such as history books. The results of this research are that according to the Islamic perspective, corruption is part of the study of jinayah fiqh and is included in the category of criminal acts. In Jinayah defines the meaning of corruption, namely Ghulul (embezzlement), Risywah (bribery), Ghasab (forcibly taking other people's rights), Sariqah (theft), Hirabah (robbery), and al-Maks (illegal levies). There are two theories of punishment in Islamic law regarding the death penalty for corruptors, namely zawajir (prevention) and jasar (coercion). In Islamic law, the death penalty can be applied in three forms, namely, qishàsh, hudud and ta`zìr.